Several Factors Responsible For Sick Building Syndrome in Urban Settings: Literature Review - Choirul Rozi; Tri Joko; Nurjazuli (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Urban dwellers are more susceptible to the adverse effects of air pollution and climate change. Sick building syndrome (SBS) relates to health issues experienced by workers as a result of indoor activities, air pollution, and climate change. The incidence of SBS is strongly correlated with environmental factors both within and outside the workplace. Objective: To identify current factors associated with the incidence of sick building syndrome in urban areas Method: Review of the literature compiled in both English and Indonesian from the databases of PubMed, Scopus, and Google Scholar. The literature, which is available in full text publications, was collected during the period of the last five years, from 2019 to 2024. Results: Temperature, relative humidity, microbes, air pollution, psychological factors, light, and ventilation in a room or workplace were some of the variables that affect the incidence of sick building syndrome in urban settings. Conclusion: SBS was related to a number of factors, including temperature, relative humidity, ventilation, lighting, pathogens, and psychosocial factors. These elements may have an individual or combined effect on worker productivity and the development of SBS.